Apoptosis of endothelial progenitor cells in a metabolic syndrome experimental model - Lembo, Carina (2012)
Aim: This study tests the hypothesis postulating that metabolic syndrome induced by chronic administration of fructose to spontaneously hypertensive rats (FFHR) generates impairment in vascular repair by endothelial progenitor cells (EPC). Materials and Methods: To characterize the vascular adverse environment present in this experimental model we measured: NAD(P)H oxidase activity, eNOS activity, presence of apoptosis in the arterial wall, all these parameters were most affected in the FFHR group. Also, we found decreased level and proliferative capacity of EPC measured by flow cytometry and colonies forming units assay in cultured cells, respectively, in both groups treated with fructose; FFHR (SHR fructose fed rats) and FFR (WKY fructose fed rats) compared with their controls; SHR and WKY. Results: The fructose-fed groups FFR and SHR also showed an incremented number of apoptotic (annexinV+/7AADdim) EPC measured by flow cytometry that returns to almost normal values after eliminating fructose administration. Conclusion: Our findings suggest that increased apoptosis levels of EPC generated in this experimental model could bein part the underlying cause for the impaired vascular repair by in EPC.